OPTIMALISASI BAHAN AJAR MATA KULIAH STATISTIKA MELALUI PEMBUATAN MODUL STUDI KASUS BERBASIS PROBLEM BASED LEARNING - Sutrisno, Sutrisno; Fauzi, Ilham Saiful; Selviana, Vuvut; Bakhrudin, Bakhrudin (Universitas Muhammadiyah Ponorogo, 2023)
In line with the goals of vocational education and the challenges of the fourth industrial revolution, Problem-Based Learning (PBL) has become one of the alternatives to enhance the quality of learning, with the hope that students can develop critical thinking skills to solve real-life problems. The approach used in this research is a development research approach based on the modified Plomp development model. Validation results indicate that the module meets the validity criteria with an average score of 3.60, with some revisions related to writing. Product testing was conducted with 24 students from 4 different classes. Research subjects were selected considering their heterogeneous cognitive abilities. Case study work was done in groups, with each group consisting of 3 students. The trial results show that the module meets practical criteria with an average score of 3.76. Therefore, the case study module for the statistics course is deemed suitable for use in learning.